Republic of Korea: 2015 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for the Republic of Korea (IMF Staff Country Reports: Country Report No. 15 / 130, 2015)
KEY ISSUES Outlook and risks. The outlook remains challenging from both a cyclical and structural standpoint. The hoped-for output recovery has not materialized-domestic demand remains sluggish and inflation low and external uncertainties have increased. More fundamentally, relatively weak non-manufacturing productivity has been accompanied by a heavy, and likely unsustainable, reliance on manufacturing exports for growth while also leaving the economy more exposed to external shocks, and the demographic headwinds from a rapidly aging population are beginning to build. Policy assessment. Building on the authorities' recent monetary, fiscal, and other policy measures to stimulate demand, efforts should remain focused on shoring up economic momentum where the currently weak outlook could have a lasting impact on Korea's growth well beyond the near term. Given asymmetric costs of the downside risk of low growth and inflation becoming entrenched the authorities should take additional pre- emptive stimulatory monetary and fiscal policy actions if clear signs of a recovery do not emerge soon. At the same time sustaining longer-term growth and reducing external imbalances call for structural reforms to address low service sector productivity, support a more dynamic corporate and SME sector, and remove barriers that lead to underutilized labor. Maintaining a flexible exchange rate is essential both as a buffer against external shocks and to facilitate adjustment toward domestic sources of growth and thereby reduce external imbalances